VIEWPOINTS OF PRESIDENT HO CHI MINH ON THE CADRES IN PART IV OF THE WORK “MODIFYING THE WAY OF WORKING” – SUGGESTIONS FOR APPLICATION IN CURRENT CADRE WORK - Nguyen Huu Anh*; Bui Thi Can; Nguyen Van Duy (Tạp chí Khoa học)
In October 1947, President Ho Chi Minh wrote Modifying the Way of Working under the pseudonym X.Y.Z in the Viet Bac war zone. This work comprises six parts, addressing most issues related to Party officials and Party personnel work. Part IV, Issues on Cadres, provides an in-depth analysis of key matters such as cadre training, educating and utilizing cadres, cadre selection, cadre treatment, and significant points in cadre policy. In the current context, studying the content of Modifying the Way of Working, particularly Part IV, is of great significance for practical application in personnel work at all levels, especially for the Party’s leadership and management cadres.